The effect of innovative activity in firm performance and development: Analysing data from eurozone - Ilias A. Makris (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose - The purpose of this paper is to examine the effect of Innovative Activity on firm performance and growth. Active Research and Development is considered to be directly related with development, prosperity and growth, in micro and macro level and a key factor in hindering economic recession. Design/methodology/approach - We analyse economic data from listed firms of selected eurozone country-members in order to associate Research and Development with performance indicators in firm and country level. For that purpose, several firm data were collected from WorldScope data base and macroeconomic data from Worldbank database. The period examined is between 2002 and 2012, with a special focus on current financial crisis (after 2007). The empirical process includes, descriptive statistics and logistic regression analysis. Findings - Findings indicate the crucial effect of innovative process in economic performance and development in firm and country level. The latter highlights the urgent need for public support in order to spur innovative activity and high-tech exports, especially in countries that were heavily affected by recession. Research limitations/implications - Some research limitations are the large number of missing cases in WordScope database, as many firms after the beginning of current crisis exit stock market. Furthermore, the other part of the economy, the Small and Medium Enterprises does not exist in the analysis, as listed firms are mainly large and mature companies. Originality/value - The results tend to highlight the need for common policy measures in eurozone, in regard to such issues, instead of imposing horizontal budgetary constraints in specific countries (like Southern Europe), hindering the vicious recessionary circle.
Keywords: M211; O39; O47; 330; Innovative Activity; Development; Firm Performance; Eurozone